Pengaruh kepemimpinan, Komunikasi Dan Motivasi Terhadap Kinerja Pegawai Dinas Pertambangan Dan Energi Oku Timur - Sri Sutandi; Zein Ghozali; Lia Sari; Masnoni; Roy Saleh (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2018)
This research aims to find out the effect of leadership to employee performance and the effect of motivation on employee performance of mining and energy services of OKU Timur. The Method of data analysis is descriptive analysis with research variables of inferential statistical analysis, path analysis, cholerity and linearity The result obtains that there is the effect of leadership on employee motivation, communication on employee multifaction, motivation on employee performance, leadership on employee performance, and communication on employee performance in OKU Timur mining and energy services. Considiresing leadership, communication and working motivation are very influential on employee perfomarmance, it is expected for the leadership to enhance his abilitiy as one of his tasks and functions as a motivator for his employees, thus employee motivation can increase because of the encouragement for recognition and feeling worthy of respect, and also the encouragement to work responsibly. In theend this can improve employee performance according to organizational expectation.